2008
DOI: 10.1002/mds.22142
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in Parkinson's disease: The cross‐sectional French DoPaMiP survey

Abstract: Pain is a frequent, but poorly studied symptom of Parkinson's disease (PD). DoPaMiP survey aimed to assess the prevalence of chronic pain in PD, to describe PD patients with chronic pain, and to record analgesic consumption. About 450 parkinsonian patients underwent structured standardized clinical examination and completed self-reported questionnaires in a cross sectional survey. Pains related or unrelated to PD were identified according to predefined criteria. About 98 patients with other chronic disorders t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
232
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(258 citation statements)
references
References 33 publications
18
232
3
5
Order By: Relevance
“…It has been suggested that strength exercises with low loads are less likely to aggravate the symptoms of illnesses such as osteoarthritis [OA] in older adults 33 . However, it is necessary to consider the possibility that training exacerbates pain and the fact that OA has been singled out as one of the most frequent causes of chronic pain in patients with PD and may be exacerbated by the disease 34 . Therefore, a careful joint assessment is recommended prior to the start of the exercise program as well as greater care during its execution, specifically with range of motion exercises, in order to avoid the worsening of pain.…”
Section: Safetymentioning
confidence: 99%
“…It has been suggested that strength exercises with low loads are less likely to aggravate the symptoms of illnesses such as osteoarthritis [OA] in older adults 33 . However, it is necessary to consider the possibility that training exacerbates pain and the fact that OA has been singled out as one of the most frequent causes of chronic pain in patients with PD and may be exacerbated by the disease 34 . Therefore, a careful joint assessment is recommended prior to the start of the exercise program as well as greater care during its execution, specifically with range of motion exercises, in order to avoid the worsening of pain.…”
Section: Safetymentioning
confidence: 99%
“…Two studies showed that the frequency of pain in PD patients was not significantly greater than that in controls (Quittenbaum and Grahn 2004;Chaudhuri et al 2006). On the other hand, 7 studies showed that the frequency of pain in PD patients was significantly greater than that in controls (Riley et al 1989;Clifford et al 1998;Etchepare et al 2006;Broetz et al 2007;Defazio et al 2008;Negre-Pages et al 2008;Beiske et al 2009;Ehrt et al 2009) (Table 1). Because there are more of the latter studies, including 2 extensive studies (Defazio et al 2008;Negre-Pages et al 2008), we think that the frequency of pain in PD patients is significantly greater than that in controls.…”
Section: Patients With Parkinson's Disease Are More Likely To Suffer mentioning
confidence: 98%
“…PD is characterized by resting tremor, slow and decreased movement (hypokinesia and akinesia), rigidity, postural instability, problems with gait, and impaired coordination. In addition to these motor symptoms, patients with PD often suffer from nonmotor symptoms, including severe pain (Riley et al 1989;Clifford et al 1998;Etchepare et al 2006;Broetz et al 2007;Defazio et al 2008;Negre-Pages et al 2008;Beiske et al 2009). …”
mentioning
confidence: 99%
“…A recent systematic review indicated a mean pain prevalence of 68% in PD patients [6], with another study finding that chronic pain complaints, especially musculoskeletal pain, were twice as likely and reported as twice as intense in PD patients compared to age-matched controls with other chronic disorders [42]. Pain often appears early in the development of PD and may be present years before clinical diagnosis [49].…”
Section: Introductionmentioning
confidence: 99%